Perception of Social Media Usage in Home Industry Product Promotion - Febrina Anandari; Jhon Veri (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Globalization is a challenge for Small and Medium Enterprises (SMEs) to continue to survive. Information Technology, especially social media, offers benefits for SMEs to improve their marketing. This study was conducted to identify the use of social media and its benefits for SMEs. This study is a descriptive observational study using the Triangulation method, which combines structured interview methods, in-depth interviews and observations of SMEs and the social media used. Subjects were selected by purposive sampling. The results of the study showed that the most widely used social media were websites, Facebook and E-mail. Social media is used by most SMEs to make personal contact with consumers, promotions/advertising, record consumer needs and convey responses to consumers. Social media is an effective communication medium for SMEs, can increase market share and help business decisions. The use of social media can increase sales volume by more than 100% if done consistently and information is updated every day. The conclusion of this study is that social media has the potential to increase market share and sales volume, so it needs to be utilized optimally and consistently.